EFFECTIVENESS OF MUSIC-BASED THERAPY AS A POSSIBLE INTERVENTION FOR DEMENTIA IN SOCIAL RESTRICTIVE SITUATIONS: A SYSTEMATIC REVIEW OF RCTS - Asyura, Muhammad MAZ; Putri, Kassie G; Chandra, Angelina P (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Patients with dementia experience painful, confusing, frustrating, and amnesialike emotional distress and instability because of their brain’s inability to correlate their emotions with the memory that causes the emotion. Moreover, the dependency of dementia patients also results in an additional emotional, physical, and financial burden to their families and caregivers. In addition, the COVID-19 pandemic forces drastic self-isolation, which are hard to comprehend for dementia patients, increasing their feeling of anxiety, loneliness, and frustration. Music therapy has gained popularity amongst other therapy alternatives for dementia for its easy accessibility, previously proven effectiveness to reduce dementia symptoms and its positive impact on the caregivers.Method: A systematic review was performed, searching for randomized controlled trials, according to the PRISMA statement, throughout five international databases with published studies up to 18 April 2021. Critical appraisal was further conducted utilizing the Cochrane Risk of Bias Tool 2.0.Results: The search yielded eight randomized controlled trials with a total of 534 subjects. The intervention conducted was in individual or group music therapy. The outcomes were measured using various indicators, and significant improvements found in agitated behaviour, behavioural and psychological symptoms, and general mood of the patient. Conclusion: Music therapy is a highly potential alternative therapy for elderly patients with dementia, showing significant and effective improvements to reduce dementia-related symptoms. Further studies in coherence with implementations of the therapy are urgently needed to aid the increasing prevalence of dementia worldwide, especially in Indonesia.